2006
DOI: 10.1002/oa.816
|View full text |Cite
|
Sign up to set email alerts
|

Congenital anomalies of the vertebral column: a case study on ancient and modern Egypt

Abstract: The aim of this paper is to identify the frequency of congenital anomalies of the vertebral column in ancient Egyptians. The material for this study consisted of 272 skeletons excavated from Giza and belonging to the Old Kingdom (the time of the early pyramid builders). The vertebral columns of these skeletons were examined for the different types of congenital anomalies that affect the vertebrae. Nine cases (3.33%) were affected with spina bifida occulta, while six cases (2.22%) had transitional vertebrae at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…Sacralization rates observed from randomly available remains of two warship crews give identical rates of 16.7% for the same number of sacra from each ship. When compared with 6.3% observed by Tague (2009), 4.2% observed by Apazidis et al (2011) and 1.5%-8% found by Masnicová and Beňuš (2003) and El-Din Sarry and El Banna (2006), there seems to be a striking difference between the findings reported here, and in most other studies rating bony fusion separately from other types. The Magora and Schwartz (1978, p. 135) study of 460 Scandinavians with 14% "complete sacralization" suggests that something related to sample population may be in effect.…”
Section: The Need To Consistently Differentiate Sacralization Typescontrasting
confidence: 95%
See 4 more Smart Citations
“…Sacralization rates observed from randomly available remains of two warship crews give identical rates of 16.7% for the same number of sacra from each ship. When compared with 6.3% observed by Tague (2009), 4.2% observed by Apazidis et al (2011) and 1.5%-8% found by Masnicová and Beňuš (2003) and El-Din Sarry and El Banna (2006), there seems to be a striking difference between the findings reported here, and in most other studies rating bony fusion separately from other types. The Magora and Schwartz (1978, p. 135) study of 460 Scandinavians with 14% "complete sacralization" suggests that something related to sample population may be in effect.…”
Section: The Need To Consistently Differentiate Sacralization Typescontrasting
confidence: 95%
“…Finally, the samples analyzed for this project are much smaller than the 2086 individuals rated by Tague (2009), the hundreds or even thousands of participants in various clinical studies, or the large collections of archeological skeletons observed by others (El‐Din Sarry & El Banna, 2006; Kim et al, 2018; Masnicová & Beňuš, 2003). By using specific criteria to identify types of LSTV, archeological collections can be more accurately described and more easily compared.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations